Sodium zirconium cyclosilicate for the management of chronic hyperkalemia in kidney disease, a novel agent. Issue 9 (2nd September 2021) - Rastogi, Anjay; Hanna, Ramy M.; Mkrttchyan, Anita; Khalid, Maham; Yaqoob, Sinan; Shaffer, Kelly; Dhawan, Puneet; Nobakht, Niloofar; Kamgar, Mohammad; Goshtaseb, Ray; Sarmosyan, Kristine; Gnarini, Mariarosaria; et al.
ABSTRACT: Introduction: Hyperkalemia is a common finding in patients with advanced kidney disease for multiple reasons. Renin-Angiotensin-Aldosterone-System Inhibitors (RAASi) that are indicated for slowing down progression of kidney disease are often associated with hyperkalemia which becomes a limiting factor in their use and titration to the maximum dose. Having a safe, effective, tolerable, and affordable potassium binder can help optimize RAAS inhibition in the setting of kidney disease. Areas covered: Although sodium polystyrene sulfonate has been a mainstay of acute management of hyperkalemia for decades, evidence regarding its efficacy is limited, and its chronic use is not routinely recommended for concerns regarding toxicity. The concern of gastrointestinal (GI) adverse effects with sodium polystyrene sulfonate has spurred the development of alternatives. Sodium zirconium cyclosilicate (SZC) is a promising agent that selectively binds potassium in the gut and eliminates it, while being safe for chronic use based on 1 year of data. Even though we do not have head-to-head studies among the three currently available binders, SZC stands out in rapidity of onset and efficacy. Expert opinion: In this review, we summarize the general management of hyperkalemia, including new agents. We review the pre-clinical and clinical data relating to sodium zirconium cyclosilicate.